Effect of Aqueous Extract of Foeniculum Vulgare on Thyroid Hormones and the Expression of its Receptors in the Ovaries of BALB/C Mice - Fatemeh Javadi; Monireh Movahedi; mahmood Barati; Seyedeh Masoomeh Amiri; Lida Kooshesh; Fereshteh Golab (Fasa University of Medical Sciences, 2020)
Background & Objective: Fennel (Foeniculum vulgare) is one of the ancient plants that has various medicinal effects. The main hormones produced by the thyroid gland are thyroxine (T4) and triiodothyronine (T3), which regulate the body's growth and development. Thyroid hormones have two receptors called TRα and TRβ in different tissues. The present study aimed to investigate the effect of fennel aqueous extract on serum levels of thyroid hormones and the expression of thyroid receptors in ovarian tissue. Materials & Methods: In this study, 40 female Balb/C mice weighing 18-20 g were used. Mice were divided into 5 groups of 8 including control, sham and intraperitoneal (IP) injection of 50, 100 and 200 mg/kg aqueous fennel extract for 14 days. The blood samples were then taken from the heart to measure thyroid hormone. The ovarian tissue was also sampled for real time thyroid receptor expression by PCR. Results: Serum thyroid hormones, T3 and T4 were not changed by aqueous extract of fennel. The expression of receptor β did not have any significant change, but the expression of receptor α increased significantly by the 200 mg/kg of aqueous extract of fennel. The weights of the rats in 200 mg/kg of fennel decreased significantly. Conclusion: Fennel may increase ovarian response to thyroid hormones in high dose.